2022
DOI: 10.1021/acsomega.2c03181
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology for the Optimization of Zn-Contaminated Soil Remediation by Soil Washing with Water-Soluble Chitosan

Abstract: Soil washing is an important method for the remediation of contaminated soil. This research presents the optimization of soil washing conditions in the remediation of Zn-contaminated soils with water-soluble chitosan (WSCS). Response surface methodology (RSM) was used to optimized the washing conditions after single factor experiments. The central composite design (CCD) with three factors and five levels was applied to the optimization of the removal efficiency of Zn from soils, and WSCS concentration, pH valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In addition, Table shows that the difference between Pred- R 2 (0.9572) and Adj- R 2 (0.9820) was within a certain range (<0.2), which indicates that the model is appropriate . A higher level of precision was also indicated by the relatively low coefficient of variation (0.7116), which also validated the reliability of the experiments . Adequate precision, which denotes the signal-to-noise ratio (a measure of the design space in predicted response relative to its error), must be greater than 4.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, Table shows that the difference between Pred- R 2 (0.9572) and Adj- R 2 (0.9820) was within a certain range (<0.2), which indicates that the model is appropriate . A higher level of precision was also indicated by the relatively low coefficient of variation (0.7116), which also validated the reliability of the experiments . Adequate precision, which denotes the signal-to-noise ratio (a measure of the design space in predicted response relative to its error), must be greater than 4.…”
Section: Resultsmentioning
confidence: 53%
“…Significant effects can be seen when the F-value is high, and the p -value is low (prob ≫ F). A probability value of p < 0.05 means that the interactions between the variables are significant and ensure the accuracy of the model. , Table presents the results of the ANOVA analysis. From Table , it can be concluded that the quadratic equation is satisfactory for predicting the relationship between the actual response and the independent variables that influence the reaction yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is essential to note that adding additional variables to the model will always increase the R 2 value, regardless of whether these variables are statistically significant or not. Therefore, it was said that a high R 2 value does not necessarily imply the adequacy of the model [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%